Effect of Tropical Environmental Pengaruh Iklim Lingkungan Tropis Pada Isolator Tegangan Tinggi - Tambi Tambi; Achmad Nur Aliansyah Ali; Agustinus lolok Agus (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2024)
The purpose of this study is to determine the relationship between tropical environmental climate and leakage current in high voltage insulators. This study describes the effect of tropical climate on outdoor insulators by considering the influence of natural tropical climate, humadity, temperature, ultraviolet rays, and rainfall in real time. leakage current data and environmental climate are obtained from monitoring for 2 years using a microcontroller. The test samples used are silicone rubber types of line post and suspension, and porcelain insulators installed in the 20kv distribution network where this test illustration can represent real conditions in the field. this leakage current test refers to the iec 60060 standard with a real-time leakage current monitoring system model and tropical climate conditions. The test results conducted when without rain show that temperature affects the leakage current flowing on the surface of the insulator because it has a significant value of 0.017 (p < 0.05), as well as uv ultra violet light also affects the leakage current because of a significant value of 0.037 (p < 0.05), but humidity partially does not affect the value of leakage current on the surface of the insulator because of its significant value of 0.721 (p>0.05), while when there is rain, the effect of rainfall on leakage current is 55.7%. so partially only rainfall